The heat treatment effects on the microstructure, hardness, and sigma phase content of L-PBF SAE 316L stainless steel - Jose M. Costa; Beatriz S. Monteiro; Francisca A. Rocha; Mariana S. Cunha; Manuel F. Vieira; Elsa W. Sequeiros (Academia Materials Science)
This research aims to enhance the understanding of the interrelationships among the manufacturing process, microstructure, and mechanical properties in the Laser Powder Bed Fusion (L-PBF) of SAE 316L stainless steel (SS), which can lead to the appearance of undesirable phases, like sigma (σ). As part of this investigation, as-built samples underwent solubilization heat treatment (HT), primarily targeting the dissolution of the σ phase and microstructure homogenization, with a subsequent assessment of its impact on hardness. The study reveals the efficacy of HT in reducing σ phase content, particularly following treatments at 950°C and 1,050°C for 2 h. Notably, the dissolution of the process-induced microstructure becomes progressively significant within the temperature range of 800–950°C for 2 h. Furthermore, the study identifies a hardening effect associated with the process-induced microstructure on the samples. Remarkably, the sample exhibiting the highest hardness value featured a substantial σ phase content and maintained the process-induced structure after HT.